Key metrics to measure the performance and impact of reusable packaging in circular supply chains - Betts, Kellen; Gutierrez-Franco, Edgar; Ponce-Cueto, Eva (Frontiers in Sustainability, 2022)
Circular supply chains comprise the industrial production and supply chain systems integral to the concept of a circular economy, which decouples economic growth from material depletion and waste generation. There are a variety of circular strategies used by companies to eliminate waste and recover value in products and materials including recycling in waste management, returns and repair in consumer-facing industries, and reusable packaging in supply chains. Packaging plays an important role in supply chains, protecting products from production to end consumers. Packaging also uses material resources and results in waste that enters our environment. Reusable packaging is one solution that may address these challenges, and successful implementation and management of this and other circular strategies requires the ability to measure and report on progress across different functions and processes. In this paper, we review the literature on metrics in circular supply chain management and reusable packaging in supply chains. We then propose a new set of metrics to measure the performance of reusing items in a circular supply chain and demonstrate the use of these new metrics with an omnichannel retail company case study. We categorize these metrics as product-level or system-level based on the level of detail they incorporate. With the case study, we found that product-level metrics facilitate the comparison of different types of reusable and single-use packages with the potential to reduce lifecycle greenhouse gas emissions. We also found that measuring system-level total logistics costs helps identify potential challenges with the feasibility of a reusable packaging system including the implications of not recovering packaging and amortizing initial costs across multiple use cycles. Our aim was to address the gap in circularity and impact metrics focused on reuse strategies in supply chains. This new set of metrics provides companies with a tool to measure and report on progress toward a circular economy. It also suggests future avenues for research to assess the economic, environmental, and social dimensions of sustainability.